An optimization model for the sizing of the biomass plants' supply chain. Issue 5 (2018) - Ferro, G.; Minciardi, R.; Podestà, E.; Robba, M.
Abstract: The exploitation of biomass in power production systems is particularly attractive to reduce CO2 emissions. However, the installation of biomass-fed power plants is not always technically and economically competitive with respect to traditional fossil fuels. This paper aims to provide a decision support system that can help the decision maker in assessing the feasibility of the plant, from a technical and economic point of view, and to provide its optimal design. The model is adapted for a plant that can produce pellets, electricity, and heat, through the gasification process. The developed model is applied to a real case study in the Alessandria Province (Italy).